Long-term virologic outcomes following bariatric surgery in patients with HIV. Issue 6 (November 2015) - Zivich, Steven; Cauterucci, Margaret; Allen, Sara; Vetter, Marion; Vinnard, Christopher
Summary: The management of morbid obesity and its metabolic complications among HIV-infected patients requires a multi-disciplinary approach, with surgical interventions as one option. We sought to assess the long-term durability of ART among HIV-infected patients undergoing bariatric procedures for the management of morbid obesity. During the study period, 7 patients underwent a bariatric surgery procedure for the management of morbid obesity: 3 patients underwent sleeve gastrectomy, 2 patients underwent laparoscopic banding, and 2 patients underwent Roux-en-Y gastric bypass surgery. Overall, the proportion of undetectable HIV viral load levels did not change after the bariatric procedures, although 2 patients did require temporary cessation of medications due to procedure-related complications. Sleeve gastrectomy and Roux-en-Y gastric bypass were safe and effective among morbidly obese HIV-infected patients in our clinic population.